DEVELOPING SCIENTIFIC EXPLANATION ABILITY OF BIOLOGY STUDENT TEACHERS BY PROVIDING EXPERIENCES IN GENERATING SCIENTIFIC EVIDENCES AND WRITING SCIENTIFIC EXPLANATIONS: การพัฒนาความสามารถในการอธิบายทางวิทยาศาสตร์ของนักศึกษาครูชีววิทยา โดยการจัดประสบการณ์การสร้างหลักฐานทางวิทยาศาสตร์และการเขียนอธิบายทางวิทยาศาสตร์ - Kamtet, Wanpen; Kruea-In, Nantarat; Wannagatesiri, Tussatrin (Journal of Education and Innovation, 2020)
The purpose of this research were to study the effect of providing experiences in generating and writing scientific explanations on the scientific explanation ability of biology student teachers and compare the scientific explanation ability of biology student teachers before and after learning. Providing these experiences based on an inquiry process. The instructor stated the problem situation for biology teacher students to formulate hypotheses, design experiments, collect data, analyze data and write scientific explanations. Research participants were 29 third year biology student teachers in tertiary level. The research instruments consisted of 1) an experimental record form, data were analyzed by content analysis for describing links among assumptions, experimental design, and scientific explanation and 2) scientific explanation ability test, data was checked by using the specific claim, evidence and reasoning rubrics. The data was analyzed by using arithmetic mean, standard deviation, and dependent sample t-test. The research results revealed that biology student teachers were able to design the experiments to generate evidences to support their experimental assumptions and used the evidences to create their own scientific explanations. After receiving feedback from the instructor, their scientific explanations were more complete. Data from scientific explanation ability test could be concluded that the mean score of scientific explanation after learning was significantly higher than before learning at 0.05.